Effects of Eldery and caregivers Preparation Program on prevention pressure sores Inpatient department Denchai Crown Prince Hospital. - In-tharawut, Busaba; Boonyanun, Yuwares (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2024)
This is a research and development design to create and study the results of the program to prepare elderly patients and caregivers to prevent pressure sores from occurring. Study in elderly people aged 60 years and over, both men and women at risk for pressure ulcers, Braden score less than 12 points.The total sample size was 32 cases. List of tools used to conduct research is a program to prepare at-risk elderly patients and their caregivers for the prevention of pressure ulcers for Inpatient Department. The study found that average knowledge score ability to take action ability to change of caregivers to prevent pressure sores in terms of skin care and cleanliness mobility assistance and taking care of food and water after developing according to the program 6 steps to prepare elderly patients and caregivers for the prevention of pressure ulcers statistically significantly higher (p < 0.05).There were no incidence of pressure ulcers in elderly patients until they were discharged The most important in patient care throughout the period after discharge from the hospital is the family caregiver. Nurses must have the competencies to provide caregivers have knowledge in making changes and be able to carry out activities to prevent infection in the elderly at risk of dependency